Desenvolvimento de "Nezara viridula" (L., 1758) (Hemiptera: Pentatomidae) em genótipos de soja - Souza, E.S.; Baldin, Edson Luiz Lopes [UNESP]; Fanella, T.L.M. (My University, 2012)
The soybean (Glycine max (L.)) has been significantly compromised by the attack of insect pests. The stink bug Nezara viridula (L.) (Hemiptera: Pentatomidae) is pointed as one of the most damaging species, reducing the quantity and quality of grain produced and requiring a large number of applications of insecticides in crops. Al-though chemical control is still the most widely used method of control, the use of resistant genotypes may represent a viable alternative in the management of this insect, reducing costs and impacts on the environment. This study evaluated the performance of nymphs of N. viridula in nine soybean genotypes under laboratory conditions (T = 25 + 2[degree]C, RH = 70 [plus or minus]10% and photoperiod = 12 h), aiming to detect possible resistance mechanisms. Thus, 25 nymphs/genotype were monitored daily by assessing the duration and mortality of the nymphal stage, the weight of nymphs and adults and the developmental period from egg to adult. The data revealed that the genotypes 'TMG-103', 'TMG-121, IAC-19', 'TMG-117', and 'IAC-24' caused 100% mortality of nymphs, indicating high levels of antibiosis and/or feeding non-preference expression. 'IAC-17' also prolonged the nymphal period, indicating the occurrence of resistance. The insects from 'PI-227687' showed the lowest average weight, also indicating the occurrence of antibiosis and/or feeding non-preference. Our results may be useful for soybean breeding programs focusing on development of genotypes resistant to insects.
Development of Nezara viridula (L., 1758) (Hemiptera: Pentatomidae) in soybean genotypes.